Work-Life Balance as the Outcome of Boundary Management among Hotel Employees: The Moderating Role of Goal-Self Concordance - Shu, Efin; Edward, Yusuf Ronny (Universitas Pendidikan Indonesia, 2023)
AbstractTourism and hotel industries position themselves to grow on after the pandemic. As the Hotel industry has entered the recovery stage, the management is back to experiencing some classic human resources issues such as long working hours, shift duties, etc. This results in a lack of Work-Life Balance (WLB) among most hotel employees. This research aims to find out if boundary management influences work-life balance moderated by goal-self concordance. This research uses Structural Equation Modeling (SEM) with Partial Least Square (PLS) version 4.0 software as the analysis tool. With the convenience sampling method, the number of samples collected is 99 employees. Data collection is conducted by distributing Google Forms to hotel employees. The data has passed all criteria of the outer model test. For the result of the inner model test, Boundary Management has a moderate level of influence on WLB by 58.6%. The result of the effect size f2 shows that Boundary Management influences WLB by 0.283. The two-tail test also shows that Boundary Management influences WLB. However, the Goal-Self Concordance does not moderate between Boundary Management and WLB. Theoretically, employees need to develop their personal goals to achieve this Balance. Practically, the hotel is recommended to improve their employees’ WLB by giving them autonomy to choose their work schedule and discuss about setting boundaries between work and family.AbstrakIndustri pariwisata dan perhotelan memposisikan diri untuk terus tumbuh setelah pandemi. Ketika industri Perhotelan telah memasuki tahap pemulihan, pihak manajemen kembali mengalami beberapa permasalahan klasik sumber daya manusia seperti jam kerja yang panjang, tugas shift, dan lain-lain. Hal ini mengakibatkan kurangnya Work-Life Balance (WLB) di antara sebagian besar karyawan hotel. Penelitian ini bertujuan untuk mengetahui apakah manajemen batasan berpengaruh terhadap work-life balance yang dimoderatori oleh goal-self concordance. Penelitian ini menggunakan Structural Equation Modeling (SEM) dengan software Partial Least Square (PLS) versi 4.0 sebagai alat analisisnya. Adanya metode convenience sampling, jumlah sampel yang dikumpulkan adalah 99 karyawan. Pengumpulan data dilakukan dengan cara menyebarkan Google Form kepada karyawan hotel. Data telah lolos seluruh kriteria uji model luar. Untuk hasil uji inner model, Manajemen Batas mempunyai tingkat pengaruh sedang terhadap WLB sebesar 58,6%. Hasil effect size f2 menunjukkan Manajemen Batas mempengaruhi WLB sebesar 0,283. Uji dua sisi juga menunjukkan bahwa Manajemen Batas berpengaruh terhadap WLB. Namun, Goal-Self Concordance tidak memoderasi antara Manajemen Batas dan WLB. Secara teoritis, karyawan perlu mengembangkan tujuan pribadi mereka untuk mencapai Keseimbangan ini. Praktisnya, pihak hotel disarankan untuk meningkatkan WLB karyawannya dengan memberikan kebebasan memilih jadwal kerja dan mendiskusikan batasan antara pekerjaan dan keluarga.